A novel through-length gradient structure assisted strength-ductility synergy in hot-rolled tungsten. (July 2022) - Li, Xingyu; Xiong, Ning; Zhang, Lin; Qu, Xuanhui
Graphical abstract: Highlights: A novel through-length gradient structure is achieved by thermo-mechanical processing strategy. Multi-aspect microstructural features include grain structure, dislocation density and crystallographic texture as spatial gradients. Through-length gradient structured tungsten possesses 120% tensile strength and 220% strain with respect to its uniformly structured counterparts. This strategy has the advantage in facile manufacture of large-scale gradient structured materials. Abstract: Gradient structured (GS) materials commonly feature varying microstructures with increasing depth from the surface. In this work, a novel through-length gradient structure (TLGS) is achieved in tungsten by a thermo-mechanical processing (TMP) strategy. The basic principle is to transfer the geometric gradient in thickness of initial compact into thickness-reduction gradient of one deformed sheet. Such thickness-reduction gradient enables formation of multi-aspect microstructural features including grain structure, dislocation density and crystallographic texture as spatial gradients. Attributing to the dual effect of work hardening and dynamic recrystallization during TMP, the gradients show a "fluctuation" characteristic with distance along length axis. Tensile tests show that the TLGS-tungsten gets benefit from its homogeneous counterparts by union. The asymmetrical deformation behavior and mechanical incompatibility can be arisen from the coexistent of disparate microstructural features, which is responsible for improved strength-ductility synergy. This strategy opens the door for facile manufacture of large-scale GS metallic materials.